Pengaruh e-money, tingkat suku bunga dan inflasi terhadap jumlah uang beredar di Indonesia - Sinta Uli Naibaho, Evi; Hodijah, Siti; Bahri, Zainul (e-Journal Perdagangan Industri dan Moneter, 2023)
This research aims to: 1) analyze developments in the money supply, e-money, interest rates and inflation in Indonesia. 2) analyze the influence of e-money, interest rates and inflation on the money supply in Indonesia. This research uses time series data, research period 2009 I-IV – 2022 I-IV. The analytical tools used are descriptive statistics and Autoregressive Distributed Lag (ARDL) regression. The results of this research show that: 1) developments in the money supply, e-money, interest rates and inflation in Indonesia fluctuate. 2) Based on the regression results, the results show that e-money, interest rates and inflation have a significant effect on the amount of money circulating in Indonesia.